From The Enlightenment Scientists Mahmudhoja Behbudii (Czech Journal of Multidisciplinary Innovations, 2024)
This article analyzes Mahmudhoja Behbudi, Jadidism, the emergence of the first Jadid schools, and the activities of enlightened scientists.